Assessment of acute liver toxicity of trigonella foenum-graecum (fenugreek) seeds aqueous extract in male mice - Hamad Alfarisi, Hamad Abdulsalam; Allow, Ahmed Kaid Naji; Hamdan, Asmah Hanim; Hamad Mohamed, Zenab B. (Elixir Publishers, 2017)
Data on acute toxicity and safety of fenugreek still not sufficient. Hence the objective of this study is to investigate the acute toxicity of fenugreek seeds aqueous extract (FSA) in vivo. Twelve male Swiss albino mice, were randomly divided into control (C), and three treatment (T1, T2, and T3) groups (n = 3 each). T1, T2, and T3 were given 3gm, 6gm, and 9gm/kg body weight FSA respectively. Intragastric divided doses of FSA were given as per OECD guidelines 425. Continuous observation of signs of acute toxicity and survival set up. Body weight was measured every 3 days, blood glucose level was measured after 6 hours, then on days 3, 7, and 14. Liver function test was measured on days 3 and 14 which is the day of sacrificing the mice. Liver was dissected and processed for histopathological examination. Administration of 9g/kg body weight of FSA showed 66.7% survival rate, while the lower FSA doses showed 100% survival. 3, 6, and 9g/kg body weight FSA failed to induce any signs of acute toxicity. Furthermore, no significant effect shown on mice body weight, blood glucose level and liver enzymes. Histologically, all FSA administered doses showed mild portal inflammation, mild mononuclear cell infiltration in hepatic parenchyma, in addition to mild bile stasis induced only in mice received 9g/kg of FSA. Conclusion: FSA showed minimum lethal oral dose and mild liver histopathological inflammatory changes